COVID-19 infection after recent heart transplantation: a case report - V. I. Vechorko; I. G. Gordeev; E. V. Gubareva; E. V. Ryndyaeva; O. V. Averkov (Российский кардиологический журнал)
History of heart transplantation in combination with immunosuppressive therapy and acute viral respiratory infection overlay makes the patient difficult to manage. In case of COVID-19, the setting is complicated by unknown pathogenesis, including its effect on blood, coagulation system, and lung tissue. Current case report discusses the 60-year-old patient with a COVID-19 infection occurred in the immediate postoperative period after heart transplantation.